Konsep strategi demonstrasi berbasis kemampuan kognitif pada mata pelajaran Komputer Jaringan di Kelas X TJK SMK Negeri 1 Seluma - Tofan Deno Syaputra; Diah Selviani; Jumiati Siska (UNIVED Press, Universitas Dehasen Bengkulu, 2021)
This study aims to determine the concept of a cognitive ability-based demonstration strategy in class X TKJ SMKN 1 Seluma. This type of research is a qualitative field research (descriptive) carried out on 25 May-31 May 2021. This research uses the following data collection techniques, interview observations, giving tests and documentation. The subjects of this study were students of class X TKJ SMKN 1 Seluma, totaling 20 people. The results of the research conducted by researchers on 20 students who used the concept of a cognitive ability-based demonstration strategy, it was found that 16 students already understood and understood how to share data on 2 laptops/pc using a LAN cable, while the other 4 students did not really understand and understand how to share data on 2 laptops/pc using a LAN cable, and are still not able to do the test questions properly and correctly so they still get scores below the KKM.